A Multi-Criteria Decision-Making Method Based Upon Type-2 Interval Fuzzy Sets For Auxiliary Systems Of A Shipâs Main Diesel Engine - BALIN, Abit (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Abstract:Â A well-qualified ship engine conductor having an effective error detection system is required to find failure as a result of which action are of immediate to be taken to prevent any possible engine impairments. Otherwise failures cumulatively can end up with crippling and irreversible profit loss. This paper proposes a fuzzy MADM methodology can help determine the most effective system for a shipâs main diesel engine. A novel interval type-2 fuzzy MADM method is chosen for the study, resting on VIKOR, to assess and employ the failure detection of auxiliary systems of a marine diesel engine. The evaluation is conducted by various groups of experts. It has been presumed that this study will also work out as a useful future maintenance process reference for marine engineering operators. All the same, the importance of the using time effectively to determine and respond to such failures is also underlined within the study. The results reveal that a fuel system is categorized as the most effective alternative followed subsequently by governor system, air supply system, and lastly cooling system. The results are grounded on the opinions expressed by three decision-making groups who put the MDEAS alternatives according to twenty ably selected criteria